2022
DOI: 10.1002/chem.202103653
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Fluorination of Acenes: Tailoring of Molecular Electronic Levels and Solid‐State Properties

Abstract: Optoelectronic properties of molecular solids are important for organic electronic devices and are largely determined by the adopted molecular packing motifs. In this study, we analyzed such structure‐property relationships for the partially regioselective fluorinated tetracenes 1,2,12‐trifluorotetracene, 1,2,10,12‐tetrafluorotetracene and 1,2,9,10,11‐pentafluorotetracene that were further compared with tetracene and perfluoro‐tetracene. Quantum chemical DFT calculations in combination with optical absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 84 publications
1
13
0
Order By: Relevance
“…The energy difference Δ E between the lowest energy optical excitation in solution and solid can be interpreted as a measure of the dielectric screening in the solid. A similar value of about 120 meV is found for both F 5 TET polymorphs, which appears reasonable in view of their comparable density, but is smaller than that of tetracene (250 meV) . To characterize the optical anisotropy of the crystals, polarization-resolved micrographs were taken.…”
supporting
confidence: 67%
See 3 more Smart Citations
“…The energy difference Δ E between the lowest energy optical excitation in solution and solid can be interpreted as a measure of the dielectric screening in the solid. A similar value of about 120 meV is found for both F 5 TET polymorphs, which appears reasonable in view of their comparable density, but is smaller than that of tetracene (250 meV) . To characterize the optical anisotropy of the crystals, polarization-resolved micrographs were taken.…”
supporting
confidence: 67%
“…The previous crystal structure analysis has shown that the molecules adopt a dipole-parallel (d-p) orientation in a crisscross packing motif (CCDC code: 1998748, depicted in Figure b,c) . Although such a stacking appears to be energetically unfavorable, powder diffraction confirms that the same packing motif also occurs in powder precipitates from the slightly polar solvent dichloromethane during the last synthetic step . Inspired by previous studies showing polymorph-selective growth by varying the solvent, ,, we extended our crystallization analysis of the polar F 5 TET also to nonpolar solvents by using the vacuum-stable silicone oil (47 V 350 Rhodorsil, VWR GmbH) for the liquid-assisted OMBD.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…This would be achieved by suppressing the short‐range interaction in these materials 71 or by increasing the direct Coulomb interaction (which we consider in our work). Chemical 7 and structural changes 72 of the organic crystal should allow the exciton separation and phonon modes to be tuned. Strategies to suppress singlet fission in organic semiconductors are not well explored, primarily because singlet fission is beneficial for photovoltaics and as such requires further study.…”
Section: Resultsmentioning
confidence: 99%